Answering the Ethical Question. (26th June 2013) - Nye, Sebastian
Abstract: Many philosophers have attempted to answer the 'ethical question': can the ethical value of an artwork ever contribute to its aesthetic value, and if so, how? In this paper, I consider a methodological question that arises out of this discussion: should attempts to address the ethical question use analytic tools found in contemporary philosophical literature, art criticism, or some combination of the two? I concur with arguments proposed elsewhere, which suggest that art criticism has an important role to play in addressing the ethical question. However, I argue that any fruitful attempt to answer the question must defend some particular way of understanding the ethical value of artworks, which suggests that we should address what I label the 'art question': what is the role and importance of art? This question, I suggest, is one with which philosophers can usefully engage. This division of labour offers a way forward in addressing this important issue.